The Evolution Health Connection-Integrating the Visitor Perspective: Significance for Evolution Education. (2nd January 2016) - Weiss, Martin; Evans, E. Margaret; Palmquist, Sasha
Abstract: The New York Hall of Science developed an exhibition, The Evolution Health Connection, in order to help visitors understand the role of evolution in their everyday life, particularly in their health. The exhibition focuses on familiar health topics—obesity, skin color, lactose intolerance and health implications related to upright posture—and invites visitors to consider the relationship between natural selection and these health issues. In order to test the validity of the assumption that an evolution exhibition related to personal health could be effective, randomly selected visitors were assigned either to visit the evolution exhibition or an exhibition on astrobiology. Responses to post-visit interviews revealed that adult and youth visitors to the evolution exhibition had a better grasp of the role of natural selection in the prevalence of health issues than did visitors to the astrobiology exhibition.